Aqueous electrodeposition and properties of tin selenide thin films - Nagalingam, Saravanan; Zainal, Zulkarnain; Kassim, Anuar; Hussein, Mohd. Zobir; Yunus, Wan Mahmood Mat (Penerbit Universiti Sains Malaysia, 2004)
Motivated by the potential applications of tin chalcogenides, investigations on these compounds are becoming particularly active in the field of materials chemistry.